SRDA: Smart Reputation-Based Data Aggregation Protocol for Wireless Sensor Network. (25th October 2015) - Li, Chaoran; Liu, Yun
Abstract : Wireless sensor network is a self-organizing multihop network, which is composed of a large number of wireless sensor nodes and usually deployed in unattended environment to collect target information. At present, WSN is facing a growing range of security threats owing to its wireless and resource-constrained characteristics. Compromised sensor nodes can easily corrupt data accuracy and integrity by falsifying sensed information, selectively forwarding or misdirecting received data packets during the process of data aggregation. To solve these security problems, we propose a smart reputation-based data aggregation protocol for WSNs (SRDA) that can provide adequate protection of data accuracy and integrity for wireless sensor network. The simulation results indicate that SRDA can effectively identify the compromised nodes and isolate them from the network by the deployment of the smart reputation system.